A study of the use of SMS cell phone technology to support teaching and learning of natural science with gr. 7 learners. - Walstra, Karen Ann (My University, 2013)
The purpose of this study was to investigate whether learners from different primary schools would respond to cell phone SMS (short message service) questions related to their schoolwork after school hours. As young people use cell phone technology to socialise, it seemed appropriate to consider integrating this technology within the school-framework, as many schools do not allow the use of cell phones during school. Another aim was to find out whether socio-economic backgrounds or gender groups responded differently to the SMS interaction study. A concurrent triangulation design research method was applied. The study examined how often and what types of answers learners would submit via SMS after school hours. The principal conclusion was that the learners reacted positively to the SMS feedback response sent in reply to an SMS answer and then engaged to a greater degree with the further questions.
Keywords: Educational technology--South Africa.; Science--Study and teaching (Elementary)--South Africa.; Text messaging (Cell phone systems)